Familial Acromegaly and Bilateral Asynchronous Pheochromocytomas in a Female Patient With a MAX Mutation: A Case Report - Mamedova, Elizaveta (Front Endocrinol (Lausanne), 2021)
BACKGROUND: There are very few cases of co-occurring pituitary adenoma (PA) and pheochromocytomas (PCC)/paragangliomas caused by MAX mutations. No cases of familial PA in patients with MAX mutations have been described to date. CASE PRESENTATION: We describe a 38-year-old female patient, presenting with clinical and biochemical features of acromegaly and PCC of the left adrenal gland. Whole-exome sequencing was performed [NextSeq550 (Illumina, San Diego, CA, USA)] identifying a nonsense mutation in the MAX gene (NM_002382) [c.223C>T (p.R75X)]. The patient had a medical history of PCC of the right adrenal gland diagnosed aged 21 years and prolactinoma diagnosed aged 25 years. Cabergoline treatment was effective in achieving remission of prolactinoma at age 33 years. The patient’s father who died at age 56 years of a heart attack had a medical history of PA and prominent acromegalic features, which supports the familial presentation of the disease. CONCLUSION: This clinical case gives an insight into the clinical presentation of familial PA and PCC probably associated with a MAX mutation.